Cakupan Perlindungan Sosial Dan Ketahanan Pangan Kunci Penanganan Stunting : Analisis Deskriptif Di Jeneponto Dan Barru, Sulawesi Selatan - Dien Abdul Munir; Sumardiyono Sumardiyono; Nur Hafidha Hikmayani (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Background: Food security and social protection are two variables that contribute to the prevalence of stunting and are critical points in efforts to prevent stunting. Programs related to food security and social protection as efforts to prevent stunting have been implemented in all districts/cities in Indonesia, including Jeneponto District and Barru District, but comprehensive information on these programs has not yet been reviewed. Objective: This study aims to describe how stunting prevention opportunities through social assistance programs for food-insecure families in Jeneponto District and Barru District can be achieved, with a focus on the effectiveness of these programs in reducing stunting. Method: The study design is descriptive and presents bivariate analysis using data on children aged 0–23 months from the 2022 Indonesian Nutrition Status Study in Jeneponto District and Barru District. Data analysis was conducted using IBM SPSS Statistics 25 and presents data percentages and categorical variables. Results: The percentage of children aged 0-23 months with stunting in Jeneponto District was 25.84% and in Barru District was 47.57%. The percentage of children with normal nutritional status was higher than those with stunting in families receiving social assistance. Conclusion: The prevalence of stunting in Jeneponto and Barru remains high. The findings indicate that targeted social assistance positively contributes to food security and stunting prevention. Most families have good dietary consumption patterns. To reduce stunting, it is necessary to integrate social assistance with food security interventions and basic health services, particularly for poor and food-insecure families with children aged 0-23 months. Keywords: Food Security, Social Protection, Stunting